Pengaruh Model pembelajaran kooperatif Tipe Student Teams Achievement Division (STAD) Terhadap Keaktifan Belajar PAK (Pendidikan agama Kristen) Siswa Kelas XI SMA Swasta PGRI 20 Siborongborong Kabupaten Tapanuli Utara Tahun Pembelajaran 2022/2023 - Zakaria Panggabean; Dorlan Naibaho; Lince R.T Simamora; Dame Taruli Simamora; Malani Simanungkalit (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this study was to determine whether there is a positive and significant effect of the cooperative learning model of Student Teams Achievement Division (STAD) Type on the Activeness of PAK Learning of XI class students of PGRI Siborongborong Private High School in the 2022/2023 Learning Year. The research method used is quantitative method with inferential descriptive data analysis. The population is all grade XI students of PGRI 20 Siborongborong High School in the 2022/2023 learning year who are Protestant Christians as many as 245 people and a sample of 49 people was determined using random sampling technique. Data were collected using a positive closed questionnaire as many as 40 items, namely 20 items for variable X and 20 items for variable Y. The results of data analysis show that there is a positive and significant effect of the cooperative learning model of Student Teams Achievement Division (STAD) Type on PAK Learning Activity of XI grade students of PGRI Siborongborong Private Senior High School in the 2022/2023 Learning Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.553> rtable (a=0.05, n=49) = 0.281. b) Significant relationship test obtained tcount = 4.555> ttable (a=0.05, dk=n-2=47) = 2.021. 2) Effect test: a) Regression equation test, obtained regression equation Y = 20.73 + 0.71X. b) Regression determination coefficient test (r2) = 30.6%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel = (a=0.05, dk numerator k = 19, dk denominator = n-2 = 49-2 = 47), namely 20.74> 1.51. Thus Ha is accepted and H0 is rejected.